Mola Hidatidosa wanita usia 43 tahun dengan kehamilan 11 minggu: Laporan kasus - cipta pramana (Unram Medical Journal, 2021)
Hydatid mole is one of the cases where the net occurs. Diagnosis of molar must be done immediately and precisely because it can become malignant and can cause seriousness due to heavy bleeding. We report a 43-year-old woman 11-weeks pregnant with complaints of vaginal bleeding. This case is interesting because the patient has a risk factor, namely 43 years old. On vaginal examination, blood was found, the external uterine ostium was open and the fundal height was felt like 24 weeks of gestation. A positive urine ?-hCG titers up to 1/400 and ultrasound on the abdomen revealed a snowstorm appearance without the fetus. Diagnosis of the hydatidiform mole is complete and then curettage is performed. The collected tissue is taken for histopathological examination. There were no complications during and after the curettage procedure. The patient came home in good condition and healthy.